论赞助人如何影响新加坡电视节目中的字幕翻译 = A study on how patronage affects the translation of subtitles in Singapore television programmes - 陈安琪 Tan, Anqi (2016)
本文将从赞助人制度分析字幕翻译的过程。 当汉语方言出现在新加坡电视节目时，译者会将其内容翻译为英文或华文或两者，然后以字幕的方式呈现给观众。这是因为新加坡政府制定的语言政策不鼓励媒体使用方言。作为赞助人，政府所制定的语言政策对字幕翻译起着限制性的作用。 本论文将从赞助制度和目的论的角度分析译者如何受到两者的限制。此外，本论文将会分析这整个过程对新加坡社会所造成的影响。 This paper aims to examine the translation of subtitles within Singapore’s television programmes with influence from patrons. The patron of Singapore’s television programmes is the government. Hence, government policies have direct implications on the content of the programmes. For example, if Chinese dialects were used, the content will need to be translated into Chinese or/and English subtitles. Applying Skopos theory and analyzing the effect of Patronage, this paper explores the relationship between patrons and subtitle translators, concluding with the effect this translation has on the Singapore society.